2016
DOI: 10.1111/aogs.13025
|View full text |Cite
|
Sign up to set email alerts
|

Cervical length at 11–40 weeks: unconditional and conditional longitudinal reference ranges

Abstract: We constructed longitudinal reference charts for cervical length in singleton pregnancies. Cervical length should be adjusted according to specific gestational-age-dependent ranges. Individualization of cervical assessment is feasible by the application of charts conditional to previous measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
2
4
1
Order By: Relevance
“…This is in accordance with a study by Kagan and Sonek 23 , who suggested that a highly curved cervix should be measured in segments to avoid underestimating CL. The slight increase in median CL is in contrast to other longitudinal CL studies 12,13,24,25 ; this might be explained by a higher proportion of very curved cervices in the first trimester. Though the possibility of a systematic overestimation of CL cannot be excluded, this seems unlikely as care was taken to train and appropriately survey CL measurements, especially with respect to correct identification of the internal os.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with a study by Kagan and Sonek 23 , who suggested that a highly curved cervix should be measured in segments to avoid underestimating CL. The slight increase in median CL is in contrast to other longitudinal CL studies 12,13,24,25 ; this might be explained by a higher proportion of very curved cervices in the first trimester. Though the possibility of a systematic overestimation of CL cannot be excluded, this seems unlikely as care was taken to train and appropriately survey CL measurements, especially with respect to correct identification of the internal os.…”
Section: Discussioncontrasting
confidence: 99%
“…As found in other studies, median CL did not change markedly from 11 to 24 weeks of gestation in the current study 12,13,24,25 . The slightly shorter median CL in the first trimester compared with the second trimester can most likely be explained by the curved shape of the cervix in the first trimester.…”
Section: Discussionsupporting
confidence: 88%
“…With respect to different techniques to measure the cervix, shorter cervixes when measured by both straight and curve techniques, do not differ substantially. In both techniques, there is a reduction of CL as the pregnancy advances [21,22]. We observed that CL reduces more significantly after 21 weeks, regardless of the technique used for assessment and this pattern is reported in literature.…”
Section: Plos Onesupporting
confidence: 81%
“…Most probably, the cervical shortening does not occur until the stress applied by the growing fetus and the myometrial contractions exceeds the biomechanical strength of the cervix. Therefore, the cervical length only changes moderately during the first two trimesters 27–30 . According to this hypothesis, women at risk of preterm birth may experience preterm cervical softening 31 before the preterm cervical shortening; as a result, the CSI may be a valuable biomarker.…”
Section: Discussionmentioning
confidence: 99%